Ultrasonic determination of thickness of masticatory mucosa: a methodologic study - Müller, Hans-Peter; Schaller, Nils; Eger, Thomas (Oral surgery, oral medicine, oral pathology, oral radiology, and endodontology, 1999)
The aim of the present study was to assess the reliability and validity of ultrasonic measurements of thickness of the masticatory mucosa.
Elektronische Reproduktion der Druck-Ausgabe
Available online 3 November 2005
Gesehen am 17.03.2021